The role of the glutathione pathway in tracheal regeneration with aortic allografts through antioxidant-driven tissue integration - Shixiong Wei; Yao Zhi; Zhou Chen; Yiyuan Zhang; Kexing Duan; Mingqian Li; Guoyue Lv (Communications Biology)
Abstract Tracheal regeneration remains a major challenge due to the lack of efficient graft integration and functional restoration. Current approaches fail to address oxidative stress-induced tissue remodeling. Here, we show that the glutathione pathway plays a pivotal role in tracheal regeneration with aortic allografts by modulating redox homeostasis and promoting host-graft integration. Through transcriptomic profiling, histological analyses, and functional assessment, we demonstrate that antioxidant-driven tissue remodeling enhances epithelialization, neovascularization, and extracellular matrix organization, thereby improving graft stability and biomechanical properties. These findings provide mechanistic insights into oxidative stress-mediated tissue remodeling and suggest that targeting redox signaling could optimize bioengineered tracheal grafts for clinical translation.